REPRODUCTIVE POTENTIAL OF THE LAKOR GOAT IN LAKOR ISLAND, SOUTHWEST MALUKU REGENCY - Carolina Jermias; Isak P. Siwa; Demianus F. Souhoka (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2021)
This study aims to determine the reproductive potential of the lakor goat in Lakor Disctrict, Southwest Maluku Regency. This research was conducted from July to August 2020 in three sample villages, namely Letoda, Sera, and Yamluli Villages. The methoud used in this study was a survey of 30 respondents of Lakor goat breeders who were determined by the simple random sampling method (simple random). The data source used in this study is primary data. The data was collected by means of observation and direct interview using a questionnaire. The results showed that the reproductive potential of the Lakor goat in the three sample villages categorized as good according to the amount of litter obtained from the type of twin birth which is quite high and the ability to give birth.